THE MODE OF ‘MUST’ IN THE MODALITY OF NECESSITY IN ENGLISH AND ITS EQUIVALENTS IN INDONESIAN - Deden Novan Setiawan Nugraha; Cece Sobarna; Sutiono Mahdi; Nani Darmayanti (Lembaga Penelitian Universitas Pasundan, 2018)
The analysis of this research basically concern issue of the cultural in the context of the mode of ‘must’ in the modality of necessity in English and its equivalents in Indonesia. The method used in this research is descriptive research method. The data taken in the form of written language manner with consideration that written manner shows more consistent characteristics in usage of the sentence structure and word choice as well. The data is taken from novels in English and also in the form of its translation in Indonesian. Syntactically, the result of the analysis shows thatthe mode of ‘must’ is actualized in modal forms (modals/modal auxiliaries) refers to ‘the rules for modal verbs’. Modal patterns, in general, used M + Vinf, where modals are always followed by infinitives or main verbs. Semantically, the mode of must is the expression of logical necessity and belongs to an epistemic modality that has a subjective meaning of certainty. The disclosure of epistemic modalities is indicated by the arising of the speaker's certainty involving his knowledge or his beliefs. The equivalent mode must in Indonesian becomes 'harus' .